PELATIHAN BAHASA INDONESIA BERBASIS PRAGMATIK UNTUK MENINGKATKAN EFEKTIVITAS KOMUNIKASI TRANSAKSIONAL DI PASAR BADUNG. - Rinayanthi (Sewagati, 2025)
Effective transactional communication is a key factor in the success of market interactions, particularly in traditional markets such as Pasar Badung, Denpasar. However, various linguistic and pragmatic challenges are still encountered in the speech acts of traders, leading to unclear messages, misunderstandings, and reduced quality of service to customers. This community service project aims to enhance traders’ pragmatic competence in using the Indonesian language through contextually designed training tailored to real market transaction situations. The method employed is participatory training using a pragmatics-based approach, covering speech act analysis, implicature, and politeness in language use. The program was conducted in three stages: needs assessment, training implementation, and evaluation of the impact on communicative behavior. The training results indicate an improvement in participants’ understanding and application of more effective and polite communication strategies during commercial interactions. The conclusion of this activity highlights that pragmatic training positively contributes to the improvement of traders’ communicative literacy, while also fostering more productive and human-centered transactional environments at Pasar Badung..